Evaluation of a 12-week Mediterranean diet-based nutritional and educational programme for breast cancer survivors: impact on BMI, fatigue, dietary adherence, and menopausal symptoms - White, Isabel; Cunningham, Joanna; Georgopoulou, Sofia; Tilt, Laura; Rawson, Rachel; Thilaganathan, Ella; Brown, Matthew R. D. (Frontiers in Nutrition, 2025)
IntroductionBreast cancer survivors commonly experience persistent symptoms after treatment. These include weight gain, fatigue, and menopausal symptoms, alongside an increased risk of long-term morbidity, including cardiovascular disease, bone loss and gut microbiome alterations. Maintaining a healthy diet is challenging due to treatment-related metabolic changes, fatigue, and dietary confusion. This research assessed the impact of a 12-week Mediterranean diet-based intervention, incorporating structured frozen meal provision and an online educational programme in breast cancer survivors. Outcomes evaluated included BMI, dietary adherence, fatigue, and menopausal symptoms. Additionally, bone, gut, and cardiovascular health within the context of survivorship was considered.MethodsA pre-post intervention evaluation design was employed. Seventy-two participants were enrolled, with 46 completing the full intervention and post-programme evaluation. The intervention comprised weekly delivery of Mediterranean diet-based frozen meals providing key nutrients. A concurrent online educational programme covered topics related to a bio-psycho-social approach to cancer rehabilitation. Primary and secondary outcomes were assessed pre-and post-intervention, educational programme engagement and adherence to meal provision were also evaluated.ResultsFollowing the intervention, BMI decreased from 26.9 to 26.3 kg/m2 (p < 0.001). Participants classified as having a healthy BMI increased from 50% at baseline to 52.2%, while the proportion classified as overweight or obese decreased from 50% to 47.8%. Mediterranean diet adherence significantly improved, with mean MEDAS scores increasing from 6.7 at baseline to 7.9 (p < 0.001). The proportion of participants with high adherence to the Mediterranean diet doubled from 8.7% to 17.4%. Menopausal symptoms significantly improved, mean scores decreasing from 23.5 at baseline to 17.5 (p < 0.001), and the prevalence of moderate symptoms reduced from 82.6% to 63%. Fatigue levels did not change significantly (p = 0.37). Subjective feedback from 28% of participants indicated perceived improvements in energy levels, citing increased consumption of fiber, omega-3 fats, and fermented foods as contributing factors. Educational programme engagement varied; 89% of participants accessed at least one module, while 40% completed all modules. Adherence to the meal provision component was high, with 79% of participants consuming at least 75% of the provided meals.DiscussionThe findings highlight the potential for dietary interventions to address key survivorship concerns.